Facile preparation and dehydrogenation of unsolvated KB3H8. Issue 80 (27th September 2017) - Zheng, Xiongfei; Yang, Yanjing; Zhao, Fengqi; Fang, Fang; Guo, Yanhui
Abstract : A convenient route was developed to produce unsolvated KB3 H8 . This compound can release hydrogen and minor boranes by subsequent cleavage of its B–H and B–H–B bonds in the 150–250 °C temperature range. And pure K2 B12 H12 can be prepared through KB3 H8 pyrolysis, which is an optional approach to produce dodecaborate compounds. Abstract : An efficient synthesis of unsolvated KB3 H8 was achieved by the reaction of a liquid K–Na alloy with BH3 ·THF at room temperature. KB3 H8 was found to release hydrogen and minor boranes by subsequent cleavage of its B–H and B–H–B bonds during pyrolysis, and yield K2 B12 H12 as a major product.